2021
DOI: 10.1177/10406387211034483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacteria in the tracheal swabs of farmed ostriches and their effect on the viability of influenza A virus

Abstract: Avian influenza surveillance is a requirement for commercial trade in ostrich products, but influenza A viruses (IAVs) have proven difficult to isolate from ostrich tracheal swabs that test positive using molecular methods. We hypothesized that microbes unique to the ostrich trachea propagate in the transport medium after sampling and affect viral viability. We cultured tracheal swabs from 50 ostriches on 4 farms in South Africa, and recovered and identified 13 bacterial, 1 yeast, and 2 fungal species. Dietzia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Respiratory affections contribute a serious hazard causing severe economic losses to the poultry industry ( Setta et al, 2018 ; Marouf et al, 2020 , 2022 ). There was no record of avian influenza infection in ostrich since the isolation of classic HPAI H5N1 2.2.1 in 2010 ( Hagag et al, 2014 ; Abolnik et al, 2019 , 2021 ). However, the new avian influenza virus isolated from ostrich belongs genetically to the HPAI H5N8 clade 2.3.4.4b viruses that have been circulated since 2016–2017 ( Kandeil et al, 2017 ; Selim et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory affections contribute a serious hazard causing severe economic losses to the poultry industry ( Setta et al, 2018 ; Marouf et al, 2020 , 2022 ). There was no record of avian influenza infection in ostrich since the isolation of classic HPAI H5N1 2.2.1 in 2010 ( Hagag et al, 2014 ; Abolnik et al, 2019 , 2021 ). However, the new avian influenza virus isolated from ostrich belongs genetically to the HPAI H5N8 clade 2.3.4.4b viruses that have been circulated since 2016–2017 ( Kandeil et al, 2017 ; Selim et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Virus isolation is still considered the "gold standard" for agent identification, where it is used primarily for diagnosis of the first clinical case and to obtain antigen for subsequent testing (OIE, 2019). Virus isolates from RT-qPCR positive ostrich field samples have been rare (Abolnik et al, 2016), but recent studies aimed at investigating the possible reasons for this determined that the standard PBS: glycerol transport medium (50 %, v/v, without antimicrobials) negatively affects AIV viability in ostrich tracheal swabs (Pieterse et al 2021) and that excluding antimicrobials from VTM encourages the growth of specific bacteria that produce metabolites with anti-viral properties (Abolnik et al, 2021). The ostrich tracheal swabs in the present study had been stored in an appropriate protein-rich VTM that included antimicrobials; therefore we used them to determine the limits of detection for virus isolation from ostrich tracheal swabs.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts at isolating ostrich-origin IAVs from RT-PCR positive specimens using ECEs have often been unsuccessful (Abolnik et al 2016 ), for various possible reasons. For example, a recent study found that bacteria present in the ostrich trachea have antiviral effects on IAV, which may partially explain the failure to isolate IAVs from RT-PCR positive tracheal swabs (Abolnik et al 2021 ). However, the possibility of a species bottleneck remains, whereby ostrich-adapted IAVs may not readily infect and replicate in chicken ECEs.…”
Section: Introductionmentioning
confidence: 99%